SDS-PAGE characterization of dialyzed protein fractions from mycobacterium tuberculosis isolates for tuberculosis biomarker screening - Githa Agripina Barokah; Korry Novitriani; Annisa Nur Hasanah; Dina Ferdiani; Fransisca Probo Setyoningrum (Institute of Computer Science (IOCS), 2026)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, in which the identification of protein profiles serves as an important approach in diagnostic research and specific antigen development. This study aimed to analyze the protein profile of dialyzed fractions from Mycobacterium tuberculosis isolates using the SDS-PAGE (Sodium Dodecyl Sulfate–Polyacrylamide Gel Electrophoresis) method. Protein isolation was carried out through sonication at 4 °C to lyse the cells and release intracellular proteins without causing denaturation. The resulting lysate supernatant was subjected to 30% ammonium sulfate precipitation to separate proteins based on their solubility, followed by dialysis to remove residual salts and unwanted small molecules. The total protein concentration was measured using a photometer with a total protein reagent, showing a relatively low value, indicating that the protein fraction was concentrated on specific molecules with higher purity. The SDS-PAGE analysis revealed the presence of a protein band with an estimated molecular weight of 77,6 kDa, suggesting the successful purification of protein fractions based on molecular weight. Based on these findings, it can be concluded that the combination of sonication, ammonium sulfate precipitation, and dialysis is effective as a preliminary purification method to obtain purer proteins from Mycobacterium tuberculosis isolates and enables more specific characterization of protein profiles through SDS-PAGE.